A novel magnetically recyclable photocatalyst of Bi12TiO20/Co composites with enhanced photocatalytic performance. Issue 17 (1st December 2017) - Wang, Yufei; Zhang, Yu; Yan, Long; Li, Jian; Wang, Chao; Fu, Feng
Abstract: Both Bi12 TiO20 and Bi12 TiO20 /Co particles were synthesized by a hydrothermal process. The as-synthesized particles were characterized by SEM and TEM for size and morphology, and the results showed the particles presented hierarchical morphology with the size of 200 nm. Both XPS and XRD results confirmed the existence of both Bi12 TiO20 and Co phases in the Bi12 TiO20 /Co particles. The photocatalytic performance of the as-synthesized particles was investigated in Rhodamine B degradation reaction under visible light irradiation. Bi12 TiO20 /Co composites showed higher photocatalytic performance than single phase Bi12 TiO20 particles, which could be attributed to the increased separation effects between photo-induced electrons and holes from. Meanwhile, the magnetic properties of Co could be used to magnetically separate and recycle the Bi12 TiO20 /Co composites after reactions. The stability testing experiment with Bi12 TiO20 /Co particles showed that the composite had a high stability over photocatalytic corrosion. The photoelectrochemistry investigation showed that the introduction of Co could increase the electron/hole separation efficiency in BTO/Co composites during photocatalytic reactions. This research proposed an effective and inexpensive way to increase the performance and recycling of Bi12 TiO20 based photocatalysts.